Rapid Colloidal Gold Immunoassay for Pharmacokinetic Evaluation of Vancomycin in the Cerebrospinal Fluid and Plasma of Beagle Dogs - Yechang Guo; Shaofeng Wang; Peiyue Li; Pan Zhang; Wei Wang (Sensors, 2023)
Vancomycin (VAN), a glycopeptide antibiotic, is the preferred therapeutic agent for treating Gram-positive bacteria. Rapid and precise quantification of VAN levels in cerebrospinal fluid (CSF) and plasma is crucial for optimized drug administration, particularly among elderly patients. Herein, we introduce a novel clinical test strip utilizing colloidal gold competitive immunoassay technology for the expedient detection of VAN. This test strip enables the detection of VAN concentrations in clinical samples such as plasma within 10 min and has a limit of detection of 10.3 ng/mL, with an inhibitory concentration 50% (IC50) value of 44.5 ng/mL. Furthermore, we used the test strip for pharmacokinetic analysis of VAN in the CSF and plasma of beagle dogs. Our results provide valuable insights into the fluctuations of the drug concentration in the CSF and plasma over a 24 h period after a single intravenous dose of 12 mg/kg. The test strip results were compared with the results obtained via liquid chromatography–mass spectrometry methods, and the measured VAN concentrations in the CSF and plasma via both of the methods showed excellent agreement.